2012
DOI: 10.1590/s1679-45082012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Circuncisão por motivos médicos no sistema público de saúde do Brasil: epidemiologia e tendências

Abstract: Objective: To evaluate the epidemiological factors associated to medical circumcision, based on data from the Brazilian public health system. Methods: Using the Unified Health System public database between 1984 and 2010, hospital admissions associated with surgical treatment of phimosis were searched. A total of 668,818 men admitted to public hospitals who underwent circumcision were identified and included in the present study. Results: A mean±standard deviation of 47.8±13.4 circumcisions/100,000 men/year wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Large nationally representative surveys were more likely to provide the most accurate estimates of MC prevalence, whereas small surveys in sub-regions of a country have the potential to generate MC prevalence data that deviate from the actual national figure. As an example, a more recent, larger national survey in Brazil found overall MC prevalence to be 1.3 % [ 48 ], noting higher figures for cities in the south compared with rural areas in the north of this country. This demonstrated that MC prevalence figures from older surveys confined to Sao Paulo [ 50 52 ] and Rio de Janeiro [ 49 ] had yielded figures higher than the national average.…”
Section: Discussionmentioning
confidence: 99%
“…Large nationally representative surveys were more likely to provide the most accurate estimates of MC prevalence, whereas small surveys in sub-regions of a country have the potential to generate MC prevalence data that deviate from the actual national figure. As an example, a more recent, larger national survey in Brazil found overall MC prevalence to be 1.3 % [ 48 ], noting higher figures for cities in the south compared with rural areas in the north of this country. This demonstrated that MC prevalence figures from older surveys confined to Sao Paulo [ 50 52 ] and Rio de Janeiro [ 49 ] had yielded figures higher than the national average.…”
Section: Discussionmentioning
confidence: 99%
“…This is because of the low prevalence of circumcision in the general population (<20%) 36 . Neonatal circumcision is not normally performed in Brazil, and regions with worse access to healthcare have a lower rate of circumcision in childhood and adulthood 37 . By comparison, in the United States, where around 80.5% of the global population is circumcised, the incidence of penile cancer is very low 38 .…”
Section: Discussionmentioning
confidence: 99%
“…When age was limited to 1 to 4 years, it was noted that 1.1% of these children were circumcised within this period. 2 …”
Section: Introductionmentioning
confidence: 99%